Strand rods and high-performance fiber-reinforced cementitious composites: alternative options for seismic retrofit of existing structures - Eshelman, Larissa D. P. (Kansas State University, 2019)
A recent increase in the frequency and spatial variety of seismic activities necessitates the need for re-evaluation of existing structures. Many existing structures do not meet the minimum code design criteria should they be impacted by a seismic event. These structures are vulnerable to damages which could result in injuries to occupants or even loss of life. In order to avoid these failures, these structures need to be rehabilitated to provide additional resistance to the lateral effects produced by seismic events. This report will briefly discuss the necessity of a seismic retrofit and the process in which it can be accomplished. It will then outline two alternative methods of seismic retrofit: strand rods and prefabricated high-performance fiber-reinforced cement composite panels. These methods have a promising future in seismic retrofit due to their ease of use, cost efficiency, and minimal interruption to the continued use of the structure.
Keywords: Seismic; Retrofit; Strand rods; HPFRCC panels